On the existence of deterministic chaos in the solar terrestrial environment - Romanelli, L. (1988)
Time series corresponding to F 10.7 solar flux, AE index and the ionospheric critical frequency f0F2 are analyzed, for periods of low solar activity, in order to find whether they show either deterministic behavior or stochastic noise. Both the correlation dimension and a lower bound of the Kolmogorov entropy are calculated. For the time series analyzed, deterministic chaos is found, and its implications are discussed.